Challenges faced by healthcare start-ups - Dr Koppala Ravi Babu,; Dr. Amrutha Reddy A, (Archives of Business Research, 2021)
Healthcare start-ups across the globe are on rise and are creating new horizon. Healthcare is evolving industry with newest technology and compliances requiring young talent and entrepreneurs to establish healthcare and tech start-ups. The present study was planned with the primary aim to analyse the challenges faced by entrepreneurs in starting and operating healthcare start-ups. A questionnaire-based survey was conducted among 50 healthcare start-up founders. A structured questionnaire containing 15 questions were used to understand the challenges faced by start-ups on health industry. The study results revealed a statistically significant association between the experience of the founder and opinion regarding the growth of start-ups in the healthcare field [c2=16.22; p=0.013]. Furthermore, there was a statistically significant association between financial aid for the start-up and consumer credibility and growth of the star-up [c2=20.19; p=0.01]. The present questionnaire survey-based study delineated that financial aid, data safety & security for electronic data are the major challenges faced by healthcare start-ups. Hence, this study supplies a vital information source for the upcoming venture healthcare start up founder to consider highlighted challenges and its impact on the success of healthcare start-ups for their successful endeavour as health care entrepreneur.